Management of fungal foliar diseases of greengram (Vigna radiata) through integrated approaches - K.B. YADAHALLI*, M.C. KAVYASHREE and (Indian Phytopathology, 2016)
Greengram is an important pulse crop affected by many foliar diseases such as Cercospora leaf spot, powdery mildew and anthracnose which are main constraints in reducing the yield due to reduction of photosynthetic activity.The integrated seed treatment and foliar spray options may help in bringing out effective and economical way to manage the foliar fungal pathogens. A field experiment was conducted during kharif, 2013 to assess the efficacy of seed treatment options involving seed dressing fungicide and bio agent along with common foliar spray of effective fungicides for the management of foliar fungal diseases. The combi fungicide, trifloxystrobin 25% + tebuconazole 50% WG @ 0.05% followed by hexaconazole 5 % EC @ 0.1 % with or without seed treatment combinations were found to be very effective in managing all the foliar fungal diseases of greengram.